Interkoneksi Teologia Doa Virtual dan Kepemimpinan Transformatif Gereja dalam Misi Digital Global - Irma Ompusunggu; Andreas Nugroho; Kornelius Rulli Jonathans (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
The interconnection between virtual prayer theology, transformative church leadership, and global digital mission is an important issue in the context of technological developments that continue to change the landscape of church ministry. The emergence of virtual prayer practices through various digital platforms has raised new theological questions about divine presence, spiritual participation, and the authenticity of the spiritual experience of the congregation. At the same time, the Church requires transformative leadership that is capable of adapting to digital changes, building a relevant vision, and facilitating the spiritual transformation of the congregation. The interconnection between virtual prayer theology and transformative leadership is an important basis for strengthening the global digital mission, especially in expanding cross-cultural and geographical ministry. This study aims to integrate these three dimensions into a comprehensive conceptual framework to assess their theological relationship and practical implications for church ministry. Using a qualitative approach through theological and leadership literature analysis, it can be concluded that the synergy between virtual prayer theology and transformative church leadership contributes significantly to effectiveness in global digital mission, enabling the church to develop digital ministry strategies rooted in Christian spirituality and the missio dei mandate. These findings emphasise the urgency of integrating theology, leadership, and digitalisation in the church's mission in the technological era.AbstrakInterkoneksi antara teologi doa virtual, kepemimpinan transformatif Gereja, dan misi digital global menjadi isu penting dalam konteks perkembangan teknologi yang terus mengubah lanskap pelayanan gereja. Munculnya praktik doa virtual melalui berbagai platform digital telah menghadirkan pertanyaan teologis baru mengenai kehadiran ilahi, partisipasi rohani, dan otentisitas pengalaman spiritual umat. Pada saat yang sama, Gereja memerlukan kepemimpinan transformatif yang mampu beradaptasi dengan perubahan digital, membangun visi yang relevan, serta memfasilitasi transformasi spiritual jemaat. Interkoneksi antara teologi doa virtual dan kepemimpinan transformatif menjadi dasar penting bagi penguatan misi digital global, terutama dalam memperluas pelayanan lintas budaya dan geografis. Penelitian ini bertujuan untuk mengintegrasikan ketiga dimensi tersebut ke dalam kerangka konseptual yang komprehensif guna menilai hubungan teologis dan implikasi praktisnya bagi pelayanan gereja. Menggunakan pendekatan kualitatif melalui analisis literatur teologis dan kepemimpinan, maka dapat disimpulkan bahwa sinergi antara teologi doa virtual dan kepemimpinan transformatif gereja berkontribusi signifikan terhadap efektivitas dalam misi digital global, sehingga gereja mampu mengembangkan strategi pelayanan digital yang berakar pada spiritualitas Kristen dan mandat missio dei. Temuan ini menegaskan urgensi integrasi teologi, kepemimpinan, dan digitalisasi dalam misi gereja di era teknologi.